The Impact of Technical Innovations and Donor-Site Mesh Repair on Autologous Abdominal-Based Breast Reconstruction—A Retrospective Analysis - Promny, Theresa; Huberth, Paula; Müller-Seubert, Wibke; Promny, Dominik; Cai, Aijia; Horch, Raymund E.; Arkudas, Andreas (Journal of Clinical Medicine, 2024)
Background: The aim of this study was to examine the potential benefit that may be achieved through the introduction of technical innovations and the incorporation of mesh for fascial donor site closure in uni- and bilateral autologous breast reconstruction with abdominal tissue. Methods: A retrospective single-center review of all breast reconstructions with a DIEP or MS-TRAM flap between January 2004 and December 2019 was performed. Donor and recipient site complications and operation times were evaluated before and after the implementation of coupler anastomoses, preoperative computed tomography angiography (CTA), indocyanine green (ICG) angiography, and the inclusion of mesh in donor site repair. Results: A total of 396 patients were included, accounting for 447 flaps. Operation time was significantly shorter in unilateral reconstructions after the implementation of CTA (p < 0.0001). ICG angiography significantly reduced the rates of partial flap loss (p = 0.02) and wound healing disorders (p = 0.02). For unilateral reconstructions, abdominal bulging or hernia was observed more often in MS1-TRAM flaps without synthetic mesh repair (p = 0.001), whereas conservatively treated seroma developed more frequently after mesh implantation (p = 0.03). Conclusions: Recent technological advancements developed over the past few decades have made a substantial impact on decreasing surgical duration and enhancing procedure safety.
CRIS-Team Scopus Importer:2024-05-03
Keywords: computed tomography angiography; coupler anastomoses; DIEP; indocyanine green angiography; MS-TRAM; perforator flaps; synthetic mesh

Vascular considerations in autologous breast reconstruction using DIEP or MS-TRAM flaps: Standard techniques, alternatives, and rescue strategies - Promny, Theresa; Arkudas, Andreas; Huberth, Paula; Horch, Raymund E. (Innovative Surgical Science, 2025)
Microsurgical breast reconstruction is an established method following mastectomy; however, various factors significantly influence the complication rate. This analysis evaluates the impact of vascular anastomosis techniques, previous surgeries, and radiotherapy on the success rate of microsurgical breast reconstruction. In a retrospective data analysis of 396 patients who underwent 447 flap procedures (single or bilateral microsurgical breast reconstruction) using tissue from the lower abdomen (either DIEP or MS-TRAM flaps), the type of venous and arterial anastomoses, the initial findings or surgical specifics at the thoracic recipient site and their influence on complications were examined. Anastomosing two veins per flap did not result in a significant reduction of major complications. Flap loss was significantly more common when standard venous anastomosis to the internal mammary vein was not used, underscoring their role as the preferred recipient vessels. No major complications were observed in patients receiving a caudal anastomosis to the internal mammary artery. Patients with prior radiotherapy exhibited an increased need for arterial revisions. All documented seromas and infections occurred in irradiated patients. A differentiated surgical plan that considers optimal anastomosis techniques, supercharging strategies, and individual risk factors is crucial to reducing complications. Further studies are needed to optimize patient-specific strategies.
CRIS-Team Scopus Importer:2025-06-06
Keywords: complications; cross over bypass; flap revision; supercharging; turbocharging